PENURUNAN LAJU PENUAAN REPRODUKSI MENCIT JANTAN (Mus muculus.Linn) DENGAN PEMBERIAN EKSTRAK JAHE (Zingiber officinale) DALAM PAKAN - Sutyarso Sutyarso; Sumayyah Annida; M. Kanedi; Hendri Busman; Nuning Nurcahyani (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2018)
The ginger rhizome contains antioxidants and is chemoprotective, therefore we suspect it can decrease the aging rate in the reproductive system. The purpose of this study, to determine the effect of ginger extract (Zingiber officinale) against reproductive aging of male mice (Mus musculus). This study, using 36 male mice (Mus musculus) aged 12-14 months, divided into three groups each 12 tails. Group 1 as controls, groups 2 and 3 were given 50 mg and 100 mg ginger extract / kg of pellets. The pellet is given for 70 days ad libitum. Next, observed the number of spermatogenic cells, as well as the number and quality of spermatozoa. The results showed that ginger extract had an effect on spermatogenic and spermatozoa (P <0,01) cells of mice. The results of preleptotene spermatocyte, pakhiten and spermatid spermatocyte counts were higher, as were the number of spermatozoa, the percentage of viability and motility, and the normal morphology of spermatozoa were more in the group given ginger extract than control (P <0.01). It was concluded that ginger rhizome extract given to mice entering the aging period could inhibit the rate of decline in reproductive function.